Characterization and lipid profile of oil from microalgae - Tejeda-Benítez, Lesly; Henao-Argumedo, Daniela; Alvear-Alayón, Mario; Castillo-Saldarriaga, Carlos Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The increasing use of biodiesel has prompted the search for new raw materials, among them are highlighted the microalgae. In this research the cultivation of microalgae Chlorella sp. and Dunaliella salina at different conditions of pH and nitrogen is reported, and the oils obtained from them characterization, in order to assess the biodiesel potential production. D. salina reached the maximun cells concentration, during a 6 days cultivation, at pH 8.5 and 0.1 mg L-1 of nitrogen, obtaining values of 1.15x106 cells mL-1, while the Chlorella sp. under a pH value of 7.5 and 0.1 mg L-1 of nitrogen conditions, achieved the maximun concentrations of 2.6x107 cells mL-1. Analysis of the fatty acid profiles revealed that the most abundant were linolenic, and then, oleic, this implies a large number of unsaturations that would have negative implications on the physicochemical properties and performance of biodiesel combustion.